„Si rex non essem, Jesuita essem” religious matters in the context of Stephen Báthory’s domestic and foreign policies in Andrzej Patrycy Nidecki’s congratulatory speeches - Mileszczyk, Robert (Melusine. Old Literature and Culture, 2024)
The aim of the dissertation is to present Stephen Báthory’s stance on religious issues and the organization of religious life in Livonia (Inﬂanty) in the light of pressure exerted on the king by various political factions and religious elites with often opposing concepts regarding the future of the territory annexed to the Commonwealth after the Treaty of Yam-Zapolsky. This goal will be achieved through the analysis of three congratulatory speeches delivered by Andrzej Patrycy Nidecki in the presence of the king in November 1579, January 1581, and August 1582.